Influence of Biophilic Knowledge on Revisit Intention: The Breeze BSD City, Tangerang, Indonesia - Aliyah, Evana Elirica; Nugroho, Agung Murti; Sufianto, Heru (Civil and Environmental Science Journal (CIVENSE), 2025)
Biophilic design has gained prominence in environmental psychology and architectural studies for its potential to improve human well-being and behavioral outcomes. However, limited research has examined how visitors’ awareness and understanding of biophilic elements influence behavioral intentions in commercial open-air environments. This study aims to analyze the effect of visitors’ knowledge of biophilic design on revisit intention at The Breeze BSD City, Tangerang, Indonesia, an open-air shopping center in Tangerang, Indonesia that incorporates nature-based features. Using a quantitative approach, the study surveyed 100 respondents and analyzed the data using simple linear regression. The results reveal a significant, positive relationship, with an R² of 38.8%, indicating that visitors’ knowledge explains a substantial portion of the variance in revisit intention. These findings highlight the importance of cognitive engagement with environmental design, suggesting that increasing visitor awareness of biophilic features can foster greater loyalty and repeat visits. The study contributes to the growing body of literature on biophilic design by emphasizing the role of user knowledge as a key psychological factor influencing place attachment and return behavior in urban commercial settings.